Pelatihan Perencanaan Keuangan Syariah Sebagai Strategi Pengelolaan Keuangan Untuk Generasi Z - Nurul Aisah; Doni Hermansyah; Bawono Ismawar (Adi Widya : Jurnal Pengabdian Masyarakat, 2023)
This Community Service aims to increase knowledge and skills in planning, compiling and managing Islamic finance for students of MAN 2 Karanganyar. The students of MAN 2 Karangayar are Generation Z who play a role in this nation. The problem faced by partners is the first, limited knowledge of sharia-based financial planning. Second, the lack of skills and ability to prepare budgets for sharia-based financial management. The solutions to these problems include: first, training to increase knowledge about sharia financial planning. Second, training in preparing an ideal budget. It is hoped that with this solution, MAN 2 Karanganyar students will be able to plan and budget for Islamic financial management so that they do not have a lifestyle with the desire to follow a trend that is currently rife or developing which can lead to hedonism and other detrimental traits. The output of this activity is increasing knowledge and increasing skills in preparing personal budgets for sharia financial management by partners.